The Independence of the Corruption Eradication Commission after the Revision of Law No. 19 of 2019: The Perspective of the Theory of Separation of Powers and Its Implications - S. M, Probo Pribadi; Simatupang, Michael Wijaya (Candela Edutech Indonesia, 2025)
After the issuance of Law No. 19/2019, which amended Law No. 30/2002 on the Corruption Eradication Commission, there were significant changes in the position and function of the KPK. The main objective of this study is to analyze changes in the position and authority of the Corruption Eradication Commission (KPK) after the enactment of Law No. 19 of 2019, whether it still fulfills the principle of independence of state institutions from the perspective of the theory of separation of powers (trias politica) as well as the legal and constitutional impacts of the transfer of the KPK to the executive branch of power on the principle of checks and balances and the effectiveness of corruption eradication in Indonesia. This research uses a normative legal research method that relies on a statutory approach and a conceptual approach. The results show that the Revision of KPK Law has serious consequences for the independence of KPK and shows significant constitutional impacts which reflect a shift in balance. The imbalance has the potential to weaken the quality of democracy while disrupting the principles of clean and accountable governance. KPK risks transforming into an administrative instrument that is vulnerable to the interests of executive power